Mastering digital photography - Freeman, Michael D. A. (Ilex, 2008)
Internationally-acclaimed photographer and bestselling author Michael Freeman presents a comprehensive thematic guide to digital photography. Freeman's own photos illustrate his thinking, with step-by-step worked examples to make the topics accessible and instructive